Exploring Safe Spaces in On-Campus Residences: Perspectives of Black and Racialized Students Through Auto-Photography - Shalan, Hend; Cheung, Shirley; Safdar, Muhammad Khalid; Ahmed, Raabia; Alrubaie, Malak; Djomga, Daniella (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
Understanding the experiences of Black and racialized students in on-campus residences is crucial, yet remains underexplored within Canadian higher education. This study employs auto-photography and photo-elicitation interview methods to examine the experiences of Black and racialized first-year students at the University of Waterloo, and to explore how on-campus residences can foster safe and inclusive spaces. Twenty participants contributed 234 photographs and 446 pages of interview transcripts. Thematic analysis revealed five overarching themes: The Intersection of Nature and Social Connections, The Importance of Connection in Creating a Sense of Belonging, Sense of Space and its Role in Well-Being and Academic Engagement, Equitable Living Spaces, and Covert Isolation. Findings highlight the role of safe spaces in promoting inclusion, well-being, and academic engagement, offering actionable insights for the University of Waterloo. This research contributes to the advancement of Equity, Diversity, and Inclusion (EDI) policies and practices within Canadian higher education on-campus living environments.